Innovation and Investment Model for the Development of Small and Medium-Sized Businesses in Ukraine - BERDAR, Marharyta M.; YAREMKO-HLADUN, Roman A. (Theoretical and Practical Research in Economic Fields, 2024)
The research topic, related to the use of an innovation and investment model in entrepreneurship, is relevant because it will contribute to the modernisation and digitalisation of the economy, which would facilitate more efficient use of information technologies and allow automating business processes. In addition, the introduction of an innovative investment model will help to create new markets and promising areas of development, which will support Ukraine’s competitiveness in the international market. The purpose of this study is to analyse innovative approaches and investments that can contribute to the growth and competitiveness of small and medium-sized businesses in Ukraine. The analytical method, statistical method, functional method, system analysis, deduction, synthesis, and comparison were used. The current state of entrepreneurship in Ukraine was analysed, including its size, structure and volume of production. Various innovative approaches and technologies that can be used by small and medium-sized enterprises for their development are revealed. The investment environment for small and medium-sized businesses is considered, including an overview of available sources of financing, the quality of the financial market, the availability of state support and other investment instruments. The main challenges faced by small and medium-sized enterprises in Ukraine in the context of the innovation and investment model are highlighted, and development prospects are considered. The practical significance lies in the use of the identified results, solving issues related to the use of an innovation and investment model in order to bring entrepreneurship to a new level.